The best of I-Witness, volume 2 - Taruc, Jose Reyes III; David, Kara S.; Aguinaldo, Sandra S.; Severino, Horacio (GMA Network, 2005)
Collection of best episodes of I witness, a documentary television show in the Philippines by GMA Network. This volume presents: the life of the students in the University Belt in Manila, the malnutrition issues in the Philippines, Maranao's karangaya or arranged marriages, and how the ethic group (Matigsalog, Dumagats and T'boli) perceive women's beauty.